Estimating the biomass of the Mt. Makiling Forest Reserve, Philippines using geographic information system - Tiburan, Cristino L., Jr.; Carandang, Myrna G.; Bantayan, Nathaniel C. (2005)
Important carbon sinks like tropical rainforests are undergoing extensive degradation all over the world. Consequently, the adverse effects of global climate change due to forest degradation are already being experienced. One approach to studying the impact of such degradation is the estimation of forest biomass. Geographic Information System (GIS) was used to determine the potential biomass of the Mt. Makiling Forest Reserve (MFR), a vital carbon sink near Metropolitan Manila. Five thematic maps were generated namely: (1) modified Weck's climate index; (2) mean annual precipitation; (3) elevation; and (5) soil texture. The total potential biomass of MFR was estimated at 1.69 Pg¹.Total actual biomass at three different periods was also estimated using land cover maps and forest inventory data. It was found that the total actual biomass for 1992, 1997, and 1999 were 1.64 Pg, 1.51 Pg, and 1.54 Pg, respectively. PBD-92, PBD-97, and PBD-99 were also generated to assess and evaluate the actual and potential biomass of various land covers in MFR. Furthermore, degradation ratios (DR) were computed for different years. Among the three different periods, it was in 1992 (DR=0.97) that degradation was found lowest compared to the other years. These results showed that the capacity of the reserve to produce biomass has not been optimized. This study is also significant in the sustainable management of MFR because it provides indispensable information that can be utilized for better planning and management operations.
Keywords: Makiling Forest Reserve (Laguna); Biomass -- Mt. Makiling Forest Reserve